Clinical Results after High-Dose Intensity-Modulated Radiotherapy for High-Risk Prostate Cancer - Valérie Fonteyne; Nicolaas Lumen; Geert Villeirs; Piet Ost; Gert De Meerleer (Advances in Urology)
Purpose. Patients with high-risk prostate cancer (PC) can be treated with high-dose intensity-modulated radiotherapy (IMRT) and long-term androgen deprivation (AD). In this paper we report on (i) late toxicity and (ii) biochemical (bRFS) and clinical relapse-free survival (cRFS) of this combined treatment. Methods. 126 patients with high-risk PC (T3-4 or PSA >20 ng/mL or Gleason 8–10) and ≥24 months of followup were treated with high-dose IMRT and AD. Late toxicity was recorded. Biochemical relapse was defined as PSA nadir +2 ng/mL. Clinical relapse was defined as local failure or metastases. Results. The incidence of late grade 3 gastrointestinal and genitourinary toxicity was 2 and 6%, respectively. Five-year bRFS and cRFS were 73% and 86% respectively. AD was a significant predictor of bRFS (P=0.001) and cRFS (P=0.01). Conclusion. High-dose IMRT and AD for high-risk PC offers excellent biochemical and clinical control with low toxicity.